FROM ADAM SMITH TO AMARTYA SEN: GLOBAL MARKET AS A POSSIBLE INSTRUMENT TO PROMOTE SOCIO-ECONOMIC DEVELOPMENT - Pagliari, Carmen; Bucciarelli, Edgardo; Alessi, Michele (Investigación Económica, 2013)
The present paper is aimed both at analyzing how Amartya Sen’s economic and moral thought is influenced by Adam Smith’s works and at offering a perspective on global market which could be investigated through quantitative analyses. In order to achievethis purpose, the authors provide a potential definition of globalization which arises not from empirical evidences but from the analysis of the links existing betwee Adam Smith’s thought and Amartya Sen’s one. Globalization is here considered firstas a global division of labour, second as a global market where the products generated by the division of labour are exchanged, and third as a complex socio-economic phenomenon which generates positive outcomes under two conditions: on one hand, every agent has to respect the rules coming from a common ethic, and, on the otherhand, countries and International Organizations have to guarantee that every agent respects national and international laws. Therefore, the perspective on globalization here presented shows how global market could be a potential instrument to promote socio-economic development.